Shakespeare’s Sonnets in Brazil: Striking a Balance Between Losses and Gains in the Translation Process - da Silva, Gisele (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractTraditional notions surrounding translation have for many centuries defined the translator’s idea of his own task as limited, mechanical, and devoid of any creativity, creativity being a characteristic of the author, not the translator. This issue is particularly at stake in the case of poetry translation, where the transporting of the combination of sound and meaning to another language becomes the one great challenge. In this article, an analysis is made of the way three Brazilian translators of Shakespeare’s Sonnets explain and deal with their own translation choices. These choices are often dictated by a negotiation process based on loss and compensation.